Analysis of Ship Arrival Inhibiting Factors on Maritime Agency Performance : A Qualitative Study at PT. Berkah Tata Baruna Banten - Junaidi Junaidi; Jaja Suparman; Natanael Suranta; Siska Yoniessa; A. Nurfajri Irwan; Fitri Mulyana (International Forum of Researchers and Lecturers, 2025)
This qualitative research investigates the critical factors inhibiting ship arrival efficiency and their impact on shipping agency performance at PT. Berkah Tata Baruna Banten Branch. Through comprehensive interviews with maritime professionals, port operators, and agency management, the study examines three primary variables: pilot tugboat services, cargo loading-unloading productivity, and document processing efficiency. Utilizing thematic analysis and narrative synthesis, findings reveal significant operational integration challenges that directly affect agency performance metrics. The research demonstrates that synchronized maritime service delivery substantially influences stakeholder satisfaction and business sustainability. Results indicate that technological integration barriers, communication gaps, and human resource development needs constitute primary obstacles to optimal port performance. Beyond identifying constraints, the study highlights how fragmented coordination between service providers creates inefficiencies that extend vessel turnaround times and increase operational costs. Respondents emphasized that transparent communication channels, standardized documentation procedures, and adequate training programs are essential to building resilient port systems. Moreover, the research shows that investment in digital platforms for real-time data sharing could accelerate clearance processes, while workforce development initiatives would ensure higher service reliability. The study contributes theoretically by developing frameworks of integrated maritime service performance and practically by offering policy-oriented recommendations to strengthen agency competitiveness. Overall, the findings provide valuable insights for stakeholders seeking to enhance Indonesia’s maritime logistics capacity, aligning operational improvements with the nation’s broader economic and global shipping ambitions.